Business efficiency: Insights from Visegrad Four before, during, and after the COVID-19 pandemic - Pavol Durana; Erika Kovalova; Roman Blazek; Klaudia Bicanovska (Economies, 2025)
Efficiency is one of the tenets in assessing the financial health of an enterprise. Ultimately, the form of asset management has a major impact on growth but also on the decline of profit. It also reveals how the enterprises are positioned within the competitive market environment. For this reason, the aim of this article is to define the level of business activity in the Visegrad Four in the pre-crisis, during-crisis and post-crisis periods of the COVID-19 pandemic. The investigation included 48,650 enterprises from Slovakia, Czechia, Poland, and Hungary over the period 2017-2023. We determined the median values of eleven business efficiency indicators separately for each country and sector. The Friedman test and Kruskal-Wallis test confirmed significant differences between years and countries. Furthermore, multiple pairwise comparisons revealed analogies between the pre-crisis and post-crisis periods, as well as similarities between the two pandemic years for the tested ratios. One can observe that the results serve as the foundation for regional and international benchmarks, particularly for enterprises from former Eastern Bloc countries.
Keywords: 330; activity ratios; assets; COVID-19; efficiency; Visegrad Four